Exposure to tobacco advertisements or promotions and smoking susceptibility among adolescents in China from 2013–14 to 2021: findings from the China National Youth Tobacco Survey - Xinying Zeng; Lin Xiao; Shiwei Liu (BMC Public Health)
Abstract Background Tobacco advertisements or promotions (TAPs) can increase smoking susceptibility, especially among adolescents.China has made great progress in reducing TAPs, but has not yet achieved a total ban.This study estimated exposure to TAPs and smoking susceptibility and their changes from 2013–14 to 2021 among Chinese adolescents and examined their association. Methods Samples of middle school (MS) students in 2013 and MS and high school (HS) students in 2021 were examined, with national and provincial representativeness. Exposure to different TAPs and non-smokers’ smoking susceptibility were determined. Multilevel logistic regression was used to assess the association between exposure to TAPs and smoking susceptibility in different age groups, and whether this exposure moderated the association between anti-tobacco messages and smoking susceptibility. Results In 2021, MS and HS students had high exposure to TAPs on TV/movies (63.8% and 68.8%) and at points-of-sale (POS; 41.3% and 38.3%), but MS students had slightly lower percentages than in 2013–14. In 2021, 9.2% of MS students and 12.9% of HS students who were non-smokers were susceptible to smoking, a 5.6% decrease compared to 2013–14 among MS students. Exposure to TAPs had positive associations with susceptibility after adjusting for covariates in all age groups. Anti-tobacco messages decreased smoking susceptibility, but TAPs moderated this association. Conclusion Students had decreasing exposure to TAPs, but exposure remained high, especially at POS and TV/movies. Non-smokers had low smoking susceptibility, and this decreased over time. Exposure to TAPs was positively associated with smoking susceptibility, especially in younger students. Exposure to TAPs also reduced the benefits of anti-tobacco messages.